Comparison and validation of a fast method for the extraction and quantification of α-linolenic, eicosapentaenoic, and docosahexaenoic fatty acids - OVIEDO CASTRILLÓN, Alejandro; QUINTERO LAVERDE, Julieth Natalia; VELÁSQUEZ RODRÍGUEZ, Claudia María; LÓPEZ MARÍN, Beatriz Estella (Vitae, 2016)
Background: Omega 3 family fatty acids are currently widely studied for the diverse effects they have on cardiovascular disease risk factors. Seafood is the main natural source of these compounds. Objetives: In this paper the accuracy is verified on the fat extraction in fish, between two methods, using one of the most employees as it is the Bligh & Dyer since 1959, compared with SOXTEC, one more updated method with more modern equipment and validated quantification method for some omega 3 fatty acids by gas chromatography. Methods: Fat extraction was performed by SOXTEC and Bligh & Dyer with the use of a Certified Reference Material (SRM 1946). After having assessed the accuracy of both systems, a quantification method of α-Linolenic, Eicosapentaenoic, and Docosahexaenoic fatty acids was validated through gas chromatography. Results: It was found that the method proposed by Bligh & Dyer in 1959 is the most accurate because it showed better recovery percentages. Also, it was found that the quantification validation method of the most important omega 3 fatty acids complies with every parameter assessed throughout the validation. Conclusions: In conclusion SOXTEC being a more modernmethod which uses the latest technology, the Bligh & Dyer is the most effective method for removing fat in fish and gas chromatography allows quantification of fatty acids with precision and accuracy as meets the evaluated parameters.